2017
DOI: 10.1038/s41598-017-17079-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Kinetics in a Pre-Clinical Model of Head and Neck Cancer

Abstract: In cancer patients, circulating tumour-derived DNA (ctDNA) levels imperfectly reflect disease burden apparent on medical imaging. Further evaluation of ctDNA levels over time is needed to better understand the correlation with tumour growth and therapeutic response. We describe ctDNA kinetics within an orthotopic, immunocompetent preclinical rabbit model of local-regionally advanced head and neck squamous cell carcinoma (HNSCC). Monitoring primary tumour and metastatic lymph node volume by computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…The estimated half-life of cfDNA in circulating blood varies from several minutes (e.g., 4 min after hemodialysis cessation) to 1-2 h. [103][104][105][106] Interestingly, clearance of fetal DNA from maternal blood occurs in a bi-phasic manner: first, a rapid phase occurs with a mean half-life of~10 min to 1 h; then, a second slow phase occurs with a mean half-life of~13 h. 107 The half-life of the ctDNA level after surgical tumor resection in a pre-clinical rabbit model of head and neck cancer was 23-52 min. 25 A serial analysis of ctDNA in patients with colorectal cancer showed a halflife of 114 min. 108 The short half-life of cfDNA is convenient for "real-time" analyses of cfDNA; it facilitates treatment response evaluations and dynamic tissue status assessments in various pathophysiological conditions; for example, tissue damage or regeneration.…”
Section: Clearance Of Cfdnamentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated half-life of cfDNA in circulating blood varies from several minutes (e.g., 4 min after hemodialysis cessation) to 1-2 h. [103][104][105][106] Interestingly, clearance of fetal DNA from maternal blood occurs in a bi-phasic manner: first, a rapid phase occurs with a mean half-life of~10 min to 1 h; then, a second slow phase occurs with a mean half-life of~13 h. 107 The half-life of the ctDNA level after surgical tumor resection in a pre-clinical rabbit model of head and neck cancer was 23-52 min. 25 A serial analysis of ctDNA in patients with colorectal cancer showed a halflife of 114 min. 108 The short half-life of cfDNA is convenient for "real-time" analyses of cfDNA; it facilitates treatment response evaluations and dynamic tissue status assessments in various pathophysiological conditions; for example, tissue damage or regeneration.…”
Section: Clearance Of Cfdnamentioning
confidence: 99%
“…23,24 Some studies suggested that analyses of cfDNA outperformed instrumental methods (such as computed tomography), required a lower tumor burden, and prolonged the time window for adopting clinical decisions. 23,25 Studies of cfDNA in oncology are predominantly devoted to clinical applications of cfDNA as a tumor biomarker. An association of cfDNA level with treatment outcome, low invasiveness of an assay, implementation of high-throughput techniques make liquid biopsy using extracellular DNA an attractive candidate for a routine test in cancer management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of this study, plasma ctDNA was detected by means of a previously validated qPCR assay based on a 58-bp E6 assay derived from the E6 open reading frame (ORF). (14) From prior studies, the 58-bp E6 assay has shown to be sensitive enough to achieve robust detection of CRPV DNA sequences form as little as 3.7 pg of VX2 genomic DNA. Speci cities for this test also remain high showing no evidence in samples of rabbits that were not inoculated with VX2.…”
Section: Quanti Cation Of Ctdnamentioning
confidence: 99%
“…With our prior work in kinetics of ctDNA following surgery as well as a novel nanoparticle based detection of CTC in a preclinical model, we sought to develop a similar model to determine the kinetics of CTC and ctDNA in response to radiation therapy. (13,14) The establishment of such a preclinical model will allow for greater understanding of the kinetics of liquid biopsies in response to radiation, which may be of signi cance as a biomarker in further development of combination therapy.…”
Section: Introductionmentioning
confidence: 99%